2022
DOI: 10.1007/s11357-021-00495-y
|View full text |Cite
|
Sign up to set email alerts
|

A naturally hypersensitive porcine model may help understand the mechanism of COVID-19 mRNA vaccine-induced rare (pseudo) allergic reactions: complement activation as a possible contributing factor

Abstract: A tiny fraction of people immunized with lipid nanoparticle (LNP)-enclosed mRNA (LNP-mRNA) vaccines develop allergic symptoms following their first or subsequent vaccinations, including anaphylaxis. These reactions resemble complement (C) activation-related pseudoallergy (CARPA) to i.v. administered liposomes, for which pigs provide a naturally oversensitive model. Using this model, we injected i.v. the human vaccination dose (HVD) of BNT162b2 (Comirnaty, CMT) or its 2-fold (2x) or 5-fold (5x) amounts and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 86 publications
(109 reference statements)
6
37
1
Order By: Relevance
“…Lay people, even those who view vaccination as protective against COVID-19, feel anxious about the possibilities and risks of taking the vaccine [ 9 , 10 , 11 ]. Unfortunately, a significant number of people around the world still refuse to receive the vaccine [ 5 , 12 ]. Vaccination hesitancy is evoked by uncertainty and perceptual disintegration as a result of misinformation and conspiracy beliefs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lay people, even those who view vaccination as protective against COVID-19, feel anxious about the possibilities and risks of taking the vaccine [ 9 , 10 , 11 ]. Unfortunately, a significant number of people around the world still refuse to receive the vaccine [ 5 , 12 ]. Vaccination hesitancy is evoked by uncertainty and perceptual disintegration as a result of misinformation and conspiracy beliefs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine-related anxiety may also be triggered by a reported cluster of anxiety-related adverse events, which take place after the administration of COVID-19 vaccines [ 21 , 22 ]. Sudden rise in blood pressure following vaccination may raise uncertainties, since it is a typical symptom of both pseudo-allergy and anxiety [ 12 ]. In fact, high anxiety among adults attending COVID-19 vaccination centers is associated with fear that terrible consequences may happen [ 6 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a preprint publication provided evidence that i. v. injection of an adenoviral vaccine might lead to platelet-adenovirus aggregate formation leading to platelet clearance and thrombocytopenia ( Nicolai et al, 2021 ). Moreover, through the infiltration of the axillary lymph nodes, the mRNA vaccines could reach the vena cava via the thoracic duct ( Dézsi et al, 2022 ). Taken together, accidental i. v. administration of a vaccine intended for i. m. administration could potentially trigger adverse events.…”
Section: The Other Side Of the Coin: Adverse Effects Of Pegmentioning
confidence: 99%
“…It was proposed that the interaction between naturally occurring anti-cholesterol antibodies and microcrystal aggregates formed by excess cholesterol trigger complement activation thereby manifesting as increased pulmonary hypertension through the release of anaphylatoxins. Furthermore, other positively charged components or the mRNA have been also identified as possible factors could activate the complement ( Dézsi et al, 2022 ). Notably, the latter study showed that incubation of the Pfizer/BioNTech mRNA vaccine with pig serum ex vivo resulted in significant elevation of C3a anaphylatoxin and sC5b-9, the terminal complement complex.…”
Section: Beyond Peg: Other Factors Involved In Anaphylaxismentioning
confidence: 99%